Cumulative trauma disorders in the upper extremities: reliability of the Postural and Repetitive Risk-Factors Index. - James CPA; Harburn KL; Kramer JF (Archives of Physical Medicine & Rehabilitation, 1997)
OBJECTIVE: This study addresses test-retest reliability of the Postural and Repetitive Risk-Factors Index (PRRI) for work-related upper body injuries. This assessment was developed by the present authors. DESIGN: A repeated measures design was used to assess the test-retest reliability of a videotaped work-site assessment of subjects' movements. SUBJECTS: Ten heavy users of video display terminals (VDTs) from a local banking industry participated in the study. SETTING: The 10 subjects' movements were videotaped for 2 hours on each of 2 separate days, while working on-site at their VDTs. MAIN OUTCOME MEASURE: The videotaped assessment, which utilized known postural risk factors for developing musculoskeletal disorder, pain, and discomfort in heavy VDT users (ie, repetitiveness, awkward and static postures, and contraction time), was called the PRRI. The videotaped movement assessments were subsequently analyzed in 15-minute sessions (five sessions per 2-hour videotape, which produced a total of 10 sessions over the 2 testing days), and each session was chosen randomly from the videotape. The subjects' movements were given a postural risk score according to the criteria in the PRRI. Each subject was therefore tested a total of 10 times (ie, 10 sessions), over two days. The maximum PRRI score for both sides of the body was 216 points. RESULTS: Reliability coefficients (RCs) for the PRRI scores were calculated, and the reliability of any one session met the minimum criterion for excellent reliability, which was .75. A two-way analysis of variance (ANOVA) confirmed that there was no statistically significant difference between sessions (p < .05). Calculations using the standard error of measurement (SEM) indicated that an individual tested once, on one day and with a PRRI score of 25, required a change of at least 8 points in order to be confident that a true change in score had occurred. The significant results from the reliability tests indicated that the PRRI was a reliable measurement tool that could be used by occupational health practitioners on the job site. Copyright (c) 1997 by the American Congress of Rehabilitation Medicine and the American Academy of Physical Medicine and Rehabilitation